2022
DOI: 10.3390/atmos13020214
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Urban Wind Speeds and Wind Power Potentials Based on Machine Learning with City Fast Fluid Dynamics Training Data

Abstract: Wind power is known as a major renewable and eco-friendly power generation source. As a clean and cost-effective energy source, wind power utilization has grown rapidly worldwide. A roof-mounted wind turbine is a wind power system that lowers energy transmission costs and benefits from wind power potential in urban areas. However, predicting wind power potential is a complex problem because of unpredictable wind patterns, particularly in urban areas. In this study, by using computational fluid dynamics (CFD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Refs. [74,75] emphasized the efficacy of ML in forecasting wind power. Considering the potential of ML to predict wind power in novel regions utilizing daily wind speed data, Demolli et al demonstrated how ML can predict wind power in various locations.…”
Section: Ann Rbf Neural Network (Rbfnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [74,75] emphasized the efficacy of ML in forecasting wind power. Considering the potential of ML to predict wind power in novel regions utilizing daily wind speed data, Demolli et al demonstrated how ML can predict wind power in various locations.…”
Section: Ann Rbf Neural Network (Rbfnn)mentioning
confidence: 99%
“…The results of their study verified the precision of ML in urban environments and emphasized the impact of neighborhood attributes, rather than the height of buildings, on the wind energy potential. They recommended that future wind energy research consider the urban morphology [74,75]. Ref.…”
Section: Ann Rbf Neural Network (Rbfnn)mentioning
confidence: 99%
“…The spatial thermal impact of individual urban structures is initially unknown and dependent on the dynamics of the urban atmosphere. Many models tried to reproduce the dynamics with the help of computational fluid dynamics (CFD) [47][48][49][50][51][52][53]. For this study, the assumption was made that there is no horizontal air mass exchange, so that the UHI forms a typical spatial pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in atmospheric science utilized machine learning to characterize the flow in simple structures such as a duct, a single rectangular body, or a blade [15][16][17][18]. However, to the best of our knowledge, the only study that considered the complexities of urban flows utilized it only above roof tops [19].…”
Section: Introductionmentioning
confidence: 99%